The brief psychotherapeutic intervention “relaxation, mental images and spirituality”: a systematic review - Manzini, Carlene Souza Silva; Damasceno, Vanessa Almeida Maia; Elias, Ana Catarina Araújo; Orlandi, Fabiana de Souza (São Paulo Medical Journal, 2020)
BACKGROUND: The brief psychotherapeutic intervention “relaxation, mental images and spirituality” (relaxamento, imagens mentais e espiritualidade, RIME) is a form of complementary and alternative health-related therapy. It is a pioneer in the matter of relating the elements of spirituality to relaxation and to visualization of mental images. OBJECTIVE: To ascertain the history, use and benefits of RIME that have been reported in the scientific literature, within different health/disease contexts. The questions that guided this study were: In what contexts has the brief RIME psychotherapeutic intervention been used? What were its benefits? DESIGN AND SETTING: Systematic review, conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, in a public university. METHODS: The BVSPsi, CINAHL, MEDLINE, SciELO, SCOPUS and Web of Science databases were searched in September and October 2018. RESULTS: The findings showed that RIME promoted resignification of the symbolic pain of the death of patients without the possibility of cure; improved quality of life within the process of dying; contributed to the quality of life of breast cancer patients with cure possibilities; contributed to the emotional wellbeing of ostomized patients; brought quality-of-life benefits for patients with head-and-neck cancer; promoted empowerment for women with breast cancer and strengthened their libido; and promoted resignification of the spiritual pain of bereaved youths, offering a satisfactory return from mourning preparation. CONCLUSIONS: It was found that RIME has a construct history based on rigorous scientific methodology, covering quality of life and spiritual, emotional and subjective wellbeing. RIME has not been used internationally and new studies within this field, with different cases, should be encouraged. SYSTEMATIC REVIEW REGISTRATION: PROSPERO ID 164211.